Transformasi Digital di D’Besto dalam Teknologi Pesanan Online - Mutiara Muliani; Olvy Yulia Oktarizal; Rita Asmawati Lubis; Vellia Sari (CV. ITTC INDONESIA, 2025)
Digital transformation has become key for companies to improve efficiency and customer experience, especially in the fast food industry. This report explores the implementation of online ordering technology at D’Besto, a company focused on innovation to meet the needs of modern customers. Through interviews with sources, we identify D’Besto’s initial steps in shifting from a traditional cashier system to a digital machine, as well as collaboration with delivery platforms such as GoFood and Grab Food to expand market reach. Although there were no significant changes in the production process, D’Besto managed to improve the quality of service and products through attractive promotions on the ordering application. Challenges faced, such as network constraints and customer criticism, were addressed with infrastructure improvements and proactive communication. D’Besto’s long-term plans include branch expansion and further development in online ordering technology. The results of this study indicate that digital transformation not only improves operational efficiency but also contributes to higher customer loyalty.